2002
DOI: 10.1016/s0022-5347(05)65036-7
|View full text |Cite
|
Sign up to set email alerts
|

Early Hospital Discharge for Intravesical Ureteroneocystostomy

Abstract: Routine surgical repair of vesicoureteral reflux can be successful with early bladder catheter removal and without stents or drains, necessitating only overnight hospitalization in the majority of patients. Ketorolac can be given safely in children with minimal risk and when combined with caudal analgesia it facilitates early discharge home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…The surgery related complication rate and contralateral reflux development in our series were 2% and 8.9% respectively, which were consistent with the literature (2,(28)(29)(30). Complications were as follows: bleeding required blood transfusion in 1 patient, hematoma under incision in 3 and prolonged hospitalization secondary to UTI in 4 patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The surgery related complication rate and contralateral reflux development in our series were 2% and 8.9% respectively, which were consistent with the literature (2,(28)(29)(30). Complications were as follows: bleeding required blood transfusion in 1 patient, hematoma under incision in 3 and prolonged hospitalization secondary to UTI in 4 patients.…”
Section: Discussionsupporting
confidence: 90%
“…There is an increasing effort to minimize the invasiveness of this open surgery. Apart from the laparoscopic technique, contemporary series report open UNC without or with 1-day catheter technique, or via inguinal incision, or bilateral extravesical with minimal ureteral dissection with no postoperative urinary retention (28,29,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…They found that patients who were "stentless" had advantages of shortened hospital stay and decreased postoperative discomfort, while no complications or failures were observed during follow-up. Miller et al [11] reviewed 113 patients who underwent OUR without ureteral stenting, and reported similar results. It is worth noticing that both studies included only simple cases, and any patient requiring ureteral tapering, bladder augmentation, a redo procedure, and so on was excluded.…”
Section: Discussionmentioning
confidence: 79%
“…Ureteral reimplantation may be required to treat vesicoureteral reflux that is high-grade or does not resolve. This procedure is the most common pediatric urologic procedure requiring hospitalization and is usually associated with a brief LOS and few complications [2][3][4][5][6]. Various perioperative management techniques have been recommended to further reduce LOS and lower hospital costs of children undergoing ureteral reimplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Various perioperative management techniques have been recommended to further reduce LOS and lower hospital costs of children undergoing ureteral reimplantation. These modifications include early removal of the urethral catheter, elimination of the use of drains, extravesicle ureteral reimplantation techniques, continuous epidural anesthesia, and the use of non-steroidal anti-inflammatory medications to reduce narcotic use [3,4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%